Resting discharge and response dynamics of horizontal semicircular canal afferents of the toadfish, Opsanus tau - Boyle, R (J Neurosci, 1990)
The response dynamics of 66 primary afferents of the horizontal semicircular canal were studied in the toadfish using sinusoidal, rotational stimuli from 0.001–10 Hz at amplitudes of 5–100 degrees/sec. Twelve afferents were also tested to constant velocity trapezoids. Responses to sinusoids were used to classify afferents into 3 broad groups: (1) low-gain afferents that maintain a relatively linear response re: stimulus velocity across most of the frequency and amplitude spectra tested; (2) high-gain afferents that have a velocity sensitivity but also show a high-frequency gain enhancement and phase advance; and (3) so-called acceleration afferents that have a response more in phase with stimulus acceleration than velocity across the tested bandwidth. The afferent's background discharge was examined in relation to its rotational response. Low-gain afferents have regular spacing of interspike intervals. High-gain and acceleration afferents have a widely variable discharge regularity that is apparently unrelated to their rotational responses. Input/output transfer models were fit to the response data to describe the low- and high-pass filtering properties of the 3 afferent groups.